Prospective for hazelnut cultivation small energetic plants outcome in Turkey: Optimization and inspiration from an Italian model. (February 2015) - Boubaker, K.; de Franchi, M.; Colantoni, A.; Monarca, D.; Cecchini, M.; Longo, L.; Allegrini, E.; Di Giacinto, S.; Biondi, P.; Menghini, G.
Abstract: In this work, an attempt to project some elements from an Italian experience in the framework of renewable energy on a similar environment in Turkey is performed. Reference is made to the program of development of small-scale biomass gasification systems and power plants in the province of Viterbo in central Italy. Most attention has been given to the different biomass feedstock suitable for gasification and renewable energy production in the eastern Black Sea region in Turkey. Graphical abstract: Highlights: Original investigation in terms of agriculture and energy experiments between two countries. Gathering conjoint classical and scientific analyses on renewable energy issues. Presenting an original optimizing scheme analyses (SFA). Outlining policy implications of agricultural patterns along with economic and social aspects.